ll,,Step-by-step explanation:
If <em>c</em> > 0, then <em>f(x</em> - <em>c)</em> is a shift of <em>f(x)</em> by <em>c</em> units to the right, and <em>f(x</em> + <em>c)</em> is a shift by <em>c</em> units to the left.
If <em>d</em> > 0, then <em>f(x)</em> - <em>d</em> is a shift by <em>d</em> units downward, and <em>f(x)</em> + <em>d</em> is a shift by <em>d</em> units upward.
Let <em>g(x)</em> = <em>x</em>. Then <em>f(x)</em> = <em>g(x</em> + <em>a)</em> - <em>b</em> = (<em>x</em> + <em>a</em>) - <em>b</em>. So to get <em>g(x)</em>, we translate <em>f(x)</em> to the left by <em>a</em> units, and down by <em>b</em> units.
Note that we can also interpret the translation as
• a shift upward of <em>a</em> - <em>b</em> units, since
(<em>x</em> + <em>a</em>) - <em>b</em> = <em>x</em> + (<em>a</em> - <em>b</em>)
• a shift <em>b</em> units to the right and <em>a</em> units upward, since
(<em>x</em> + <em>a</em>) - <em>b</em> = <em>x</em> + (<em>a</em> - <em>b</em>) = <em>x</em> + (- <em>b</em> + <em>a</em>) = (<em>x</em> - <em>b</em>) + <em>a</em>.
Answer:
0.9222222222222222/1
Step-by-step explanation:
Answer:
Can't see the picture because old computer but isn't 16 minus 17 = -1 (negative 1)
Step-by-step explanation:
Multiplying fractions by whole numbers:
1. You have to convert the whole number into an improper fraction.
2. You then multiply the fractions straight across.
Ex: 2/3 × 6 =2/3 × 6/1 = 2×6/3×1= 12/3= 4